Developing human tissue engineered arterial constructs to simulate human in vivo thrombus formation. (31st December 2023) - Ranjbar, Jacob; Yang, Ying; Harper, Alan G.S.
Abstract: Thrombus formation is highly dependent upon the physico-chemical environment in which it is triggered. Our ability to understand how thrombus formation is initiated, regulated, and resolved in the human body is dependent upon our ability to replicate the mechanical and biological properties of the arterial wall. Current in vitro thrombosis models principally use reductionist approaches to model the complex biochemical and cellular milieu present in the arterial wall, and so researcher have favored the use of in vivo models. The field of vascular tissue engineering has developed a range of techniques for culturing artificial human arteries for use as vascular grafts. These techniques therefore provide a basis for developing more sophisticated 3D replicas of the arterial wall that can be used in in vitro thrombosis models. In this review, we consider how tissue engineering approaches can be used to generate 3D models of the arterial wall that improve upon current in vivo and in vitro approaches. We consider the current benefits and limitations of reported 3D tissue engineered models and consider what additional evidence is required to validate them as alternatives to current in vivo models.